Evaluation and Diagnosis of HIV-Associated Lung Disease - Maximous, Stephanie; Huang, Laurence; Morris, Alison (Seminars in Respiratory and Critical Care Medicine, 2016)
There are myriad pulmonary conditions associated with HIV, ranging from acute infections to chronic noncommunicable diseases. The epidemiology of these diseases has changed significantly in the era of widespread antiretroviral therapy. Evaluation of the HIV-infected patient involves assessment of the severity of illness and a thorough yet efficient pursuit of definitive diagnosis, which may involve multiple etiologies simultaneously. Important clues to a diagnosis include medical and social history, demographic details such as travel and geography of residence, substance use, sexual practices, and domiciliary and incarceration status. CD4 cell count is a tremendously useful measure of immune function and risk for HIV-related diseases, and helps narrow down the differential. Careful history of current symptoms and physical examination with particular attention to extrapulmonary signs are crucial early steps. Many adjunctive laboratory studies can suggest or rule out particular diagnoses. Pulmonary function testing (PFT) may aid in characterization of several chronic noninfectious illnesses accelerated by HIV. Chest radiograph and computed tomography (CT) scan allow for classification of diseases by pathognomonic imaging patterns, although many infectious conditions present atypically, particularly with lower CD4 counts. Ultimately, definitive diagnosis with sputum, bronchoscopy with bronchoalveolar lavage, or lung tissue is often needed. It is of utmost importance to maintain a high degree of suspicion for HIV in otherwise undiagnosed patients, as the first presentation of HIV may be via an acute pulmonary illness.
Keywords: HIV; AIDS; pulmonary diseases; diagnosis; CD4 count; chest radiograph; sputum; bronchoscopy